The committed - Nguyen, Viet Thanh, 1971- (Grove Press, 2021)
"The astonishing sequel to The Sympathizer, winner of the 2016 Pulitzer Prize in Fiction, The Committed follows the "man of two minds" as he comes to Paris as a refugee. There he and his blood brother Bon try to escape their pasts and prepare for their futures by turning their hands to capitalism in one of its purest forms: drug dealing. No longer in physical danger, but still inwardly tortured by his reeducation at the hands of his former best friend, and struggling to assimilate into a dominant culture, the Sympathizer is both charmed and disturbed by Paris. As he falls in with a group of left-wing intellectuals and politicians who frequent dinner parties given by his French Vietnamese "aunt," he finds not just stimulation for his mind but also customers for his merchandise-but the new life he is making has dangers he has not foreseen. Both literary thriller and brilliant novel of ideas, The Committed is a blistering portrayal of commitment and betrayal that will cement Viet Thanh Nguyen's position in the firmament of American letters"--